The Blessed Isles and Counterfactual History in Sallust - Gerrish, Jennifer (Histos, 2018)
Sallust’s digression on the Blessed Isles in the Histories is an exercise in ‘what if?’ or counterfactual history. Sertorius dreamed of flight to the Isles. He never went, but what if he had? Pompey would not have been granted proconsular imperium to wage the Spanish War; this was an unlawful honour, and the first of many. Sallust invites us to imagine a different history in which Pompey’s early career was constrained by law and custom, and which, in turn, did not open the door for Octavian’s equally transgressive rise to power.